O abandono de animais domésticos no munícipio de são luís-ma e seus impactos socioambientais - DUARTE, Aldenice Correa (2022)
In Maranhão, there is a large gap between what is recommended by public policies and effective actions aimed at abandoned animals. Although the State Animal Protection Law (nº 10.412, of 2016) determines some fundamental objectives in the care of the animal cause, it is very common to witness irresponsibility on the part of some individuals who abandon their domestic animals, causing serious problems to the animals. animals and public health. In this sense, the research is justified in view of the need to understand public policies and actions of society that aim to consider the risks and aggravating factors of the abandonment of dogs and cats in the Municipality of São Luís, and from this understanding to emphasize the analysis and characterization of the areas involved with this theme. This study starts from the hypothesis that there is an ineffectiveness of public policies aimed at the protection of domestic animals, as well as that there are several points of abandonment of these animals on public roads, which, consequently, is affecting the health of these animals as well as human health. Given this situation, this study aims to analyze the environmental impacts derived from the abandonment of dogs and cats in the Municipality of São Luís-MA. Using quantitative-qualitative research, the study used Content Analysis as a methodological tool for data analysis. In view of the results obtained through the interviews and field activities carried out, it can be concluded that there are several abandoned areas and inadequate shelter in the municipality of São Luís; some shelters were established in environments with a lack of infrastructure and with little security, both for the animals and for the Protectors; there are many abandoned animals in the street markets of São Luís. At the time of the research, there was no active public policy aimed at more effective reception in public shelters; in the same period, there was no support for public bodies dedicated to the animal cause; one of Organs public agencies interviewed supports itself through consultations, exams, surgeries and hospitalizations; and the “mobile castra” was found disabled. It was also possible to evidence a direct contact between the population and the abandoned animals, thus enabling the transmission of zoonoses. It was found as main causes for the abandonment of animals: economic factors, change of residence on the part, change in the behavior of the animal, unwanted procreation, or even the simple fact that the animal is female. During the COVID-19 pandemic, between 2019 and 2021, there was an increase in the number of abandoned domestic animals. And through the evidence highlighted in this study, it is understood the need for a closer look at this problem, given the possibility of impacts on the health of the human population and other animals that are healthy and living in the host spaces.